BSF maggot and Azolla pinnata based poultry feed processing to improve the economy ressilience - Andrew Setiawan Rusdianto; Fani Fahrurrijal Al Farizi; Erika Dwi Silawati; Nurul Aisyah; Alma Tsabita Kamilah; Maesarani Salsalina Sitepu; Tabah Aji Pamungkas; Rindi Mayang Sari; Aminatuz Zuhriyah; Susi Susanti; Lubna Rahman (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The Tirto Bakti II Farmers Group faces challenges in the poultry farming sector, including high feed prices and the need for nutritionally appropriate feed. Additionally, soybean waste in this village has not been optimally utilized. The Mahasiswa Berdesa program aims to develop poultry feed based on Black Soldier Fly (BSF) maggot, Azolla pinnata, and soybean meal with nutrients that meet poultry needs, while also improving the local economy through the sale of products derived from BSF maggot, Azolla pinnata, and soybean meal as poultry feed. The implementation method in this program includes training and mentoring in alternative feed processing. The results of this program indicate an increase in poultry feed production, with protein content reaching 12 percent and a selling price of IDR 8,400. This alternative poultry feed innovation contributes to reducing feed costs for farmers and promotes the sustainable utilization of local resources in the village. The implementation of this program has implications for increasing community capacity in feed production, creating opportunities for entrepreneurship among villagers, and encouraging the replication of similar initiatives in other rural areas to enhance local food security and economic resilience.